2021
DOI: 10.1123/jsr.2020-0334
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Blood Flow Restriction on Muscle Activation During Dynamic Balance Exercises in Individuals With Chronic Ankle Instability

Abstract: Context: Dynamic balance exercises are commonly utilized during ankle sprain and chronic ankle instability (CAI) rehabilitation. Blood flow restriction (BFR) has been used to enhance muscle activity during exercise and improve outcomes of traditional rehabilitation exercises in clinical populations. Objective: Examine the effects of BFR on lower-extremity muscle activation during dynamic balance exercises in individuals with CAI. Design: Crossover study design. Setting: Laboratory. Patients or Other Participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Unexpectedly, we found no between-group difference in YBT reaching distances in all directions examined following a 4-week intervention. This result differs from the finding of a previous study that showed that dynamic balance exercise with BFR-induced large-to-small increases muscle activation of the ankle muscles and increased postural stability and exertion in individuals with CAI compared with the control ( Burkhardt et al, 2021 ). This discrepancy in results may be because of the differences in methodology (i.e., training protocols and outcome measures) and participant characteristics (athletes vs. sedentary) among studies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Unexpectedly, we found no between-group difference in YBT reaching distances in all directions examined following a 4-week intervention. This result differs from the finding of a previous study that showed that dynamic balance exercise with BFR-induced large-to-small increases muscle activation of the ankle muscles and increased postural stability and exertion in individuals with CAI compared with the control ( Burkhardt et al, 2021 ). This discrepancy in results may be because of the differences in methodology (i.e., training protocols and outcome measures) and participant characteristics (athletes vs. sedentary) among studies.…”
Section: Discussioncontrasting
confidence: 99%
“…At present, the precise mechanisms underlying BFR-induced strength gain in patients with CAI are unknown. However, most recent studies ( Burkhardt et al, 2021 ; Killinger et al, 2020 ) have demonstrated considerable muscle activations during acute resistance exercise or dynamic balance exercise with BFR in individuals with CAI compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, low external load demand in BFR training allows it to benefit both healthy people and load compromised populations in need of rehabilitation [17,18]. Furthermore, more recent research has documented that BFR training may increase muscle activation both in sports training [19,20] and sports rehabilitation [21,22]. Therefore, some recent studies have applied the BFR method to CAs (BFR-CAs) and found enhanced athletic performance as a result of greater PAP [6,23].…”
Section: Introductionmentioning
confidence: 99%